Kematangan Beragama dalam Film Perjalanan Pembuktian Cinta: Sebuah Refleksi - Vivi Aniq Auvia Hidayani (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2025)
Film is meaning-filled audio-visual communication medium. Textual and visual reality serves as a platform for discussing problems and even as an affective medium for a change. Religion is one of the topics of plural society that are brought up in the movie. The thesis of religious maturity lends credence to this qualitative descriptive investigation. The purpose of this study is to use movies to analysis and assess religious maturity. The Journey to Prove Love movie, which is scheduled for release in 2024, is the subject of this study. The findings were obtained by using Peirce's trichotomy of meaning, which was developed by contemporary linguist Charles Sanders Peirce, to semantic semiotic analysis. The results of this research were as follows: First, religious maturity has a positive impact on individual resilience to life's trials and problems. Second, each individual has a unique personal dynamic and the same goes for their religious experiences. Third, the individual's ability to integrate religious values ​​with all other aspects of life results in the individual having a broader view of religion. Fourth, a person's level of religious maturity is reflected in their attitudes and decision-making abilities. The results of this research can be used as data to examine more deeply the Islamic values ​​contained in the film Journey to Prove Love.